Sexuální chování, orientace, identifikace, preference a role - Valentová, Jaroslava (Lidé města, 2004)
Commonly debated in the public sector as well as in academic circles and scientific research, the basic concepts of the phenomenon of sexual orientation are being confused or simply recognized inadequately. This especially affects the conceptual understanding of sexual behaviour, sexual orientation, but also sexual identification and sexual identity. Homosexual behaviour does not have to correspond to or be the cause of homosexual orientation. Homosexual behaviour may not necessarily be an indication of homosexual orientation. Homosexual orientation has deeper biological roots than homosexual behaviour, which, in humans, is strongly influenced by culture. The phenomenon of sexual orientation does not have to be perceived as a positively dichotomous occurrence anymore. Quite the opposite, it seems it is a continuum of various sexual orientations that can have their own specific biological and socio-cultural roots. The psychological concept of the sexual identification process suggests there can be a discrepancy between the psychological and the biological aspect of a single phenomenon, a discrepancy between sexual orientation [with no regard to behaviour] and sexual identification. The second part of the article seeks to outline the complex issue of gender conformity and nonconformity, which is closely related to the topic of homosexual orientation and, furthermore, is significantly overshadowed hy numerous 'popular myths', common among laymen. ln gender nonconformity we distinguish between Childhood Gender Nonconformity [CGN] appearing before puberty and Continuous Gender Identity [CGI]. Childhood gender nonconformity is one of the most common [although not completely accurate] predictors of future homosexual orientation. As far as the 'popular myths' connected withthis issue are concerned, the most widespread yet overly simplified idea is that every homosexually oriented male is positioned nearer to the feminine end of the masculinity-femininity scale. The article aims to illustrate that the problem is in reality more complex: actually, it is possible to distinguish more types of male homosexual orientation.